EFL Teachers’ Perceptions of Kahoot as an Online Learning Platform in Promoting Basic English Vocabulary - Situmorang, Ketlin Melisa; Simajuntak, Debora Chaterin (JOLLT Journal of Languages and Language Teaching, 2023)
This study aims to investigate teachersâ€™ perceptions of the effectiveness of using the Kahoot application in enhancing students’ vocabulary knowledge and increasing learning engagement. The research employed a qualitative research design, specifically utilizing a narrative inquiry approach to collect data. The study’s participants were teachers with prior experience using the Kahoot application. Data were gathered through the use of storytelling, where the researchers listened to and transcribed the participants’ accounts of their experiences. The findings suggest that the Kahoot application is a valuable tool for teaching vocabulary to English language learners. Teachers can leverage Kahoot to promote dynamic engagement in the learning process, which, in turn, motivates students to participate eagerly. Kahoot’s enjoyable assessment features provide teachers with a platform to facilitate vocabulary learning in a more effective manner. The participants’ experiences indicate that the majority of students respond positively to the use of Kahoot to enhance their vocabulary knowledge and express an interest in continuing to learn using this application.